REFORMA AL CÓDIGO ORGÁNICO GENERAL DE PROCESOS EN LOS EFECTOS DE LA FALTA DE COMPARECENCIA DEL ACTOR A LAS AUDIENCIAS, PARA QUE NO PROCEDA EL ABANDONO, POR LAS CAUSAS DE FUERZA MAYOR O CASO FORTUITO - LEÓN VILLACRÉS, JHOMAYRA KASANDRA (2019)
The Constitution of the Republic of Ecuador establishes the basic guarantees of due process in addition to the constitutional rights enjoyed by all citizens. In addition, the General Organic Code of Procedure stipulates the abandonment that is carried out because the parties do not move forward in the process within 80 days. Article 87 paragraph 1 of the General Organic Code of Processes establishes the abandonment, for the non-attendance of the person who presented the demand to the audience. Article 82, paragraph 2, of the aforementioned code states that due to unforeseen circumstances or force majeure affecting the conduct of the hearing, the judge may suspend the hearing and determine the term for its resumption, which may not be longer than 10 days, according to the norm, the hearing is suspended for the aforementioned cases but it does not stipulate the opportunity to justify the non-attendance of the actor at the hearing, creating a legal vacuum within the law that violates the author's rights, since if, once the hearing is installed, these events occur, the hearing is suspended and it does not estimate if the same facts arise before this diligence is accomplished. In addition, the Organic Code of Judicial Function makes reference to the fact that the judge and the lawyers can justify their non-attendance at the hearing, in the case of a fortuitous case or force majeure and thus be exempt from a sanction. However, evidencing an inequality of rights for the authors, since they are not provided with the justification in case, they cannot attend either by force majeure or fortuitous event. 5 For this reason, the importance of a "reform to the General Organic Code of Processes in the effects of the failure of the plaintiff to appear at hearings, so that abandonment does not proceed, for reasons of force majeure or fortuitous case" with the purpose of guaranteeing the plaintiff's right to equality while respecting his constitutional rights, presenting a justification duly certified by the responsible entity in case of presenting a problem of force majeure or fortuitous case and the abandonment is not declared. Reason for which, the present investigative work has been proposed, in which it is proposed to elaborate a project of reform to the General Organic Code of Processes concerning the abandonment due to the non-attendance of the actor to the audiences.